Development of Information Systems Models Management for Students - Ikhwan, Subaiki; Mukhtar, Mukhneri; Wahyudi, Mochamad (Universitas Malikussaleh, 2019)
Student management is an important part that must be considered by schools. The government has made standardized rules for how schools can manage students so that they are in accordance with National Education Standards. Student management activities start from registration, until student services that have been arranged neatly, may not run optimally, if schools are still manual in tidying student data collection. By him the role of student management information systems is very important for every school to have. This study aims to determine how schools can create student management information systems that are feasible and effective.